Improvement of Integrated Thematic Learning Process Tema 3 with Problem Based Learning Model in Class IV Elementary School - Tiara Septiaqlima; Reinita Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research was conducted based on the facts indicating that the integrated thematic     learning was not run as it was expected. The teacher seemed to ignore the involvement of the learners in making correlation between the laerning materials and their real life. The purpose of   this research  was  to  describe the application  of PBL model  in integrated thematic learning process. The technique used is observation. This research is a class action. This research was conducted at SDN 15 Ulu Gadut Kota Padang. The subject of the research was the teacher and the learners of class IV totaling 24 people . The result of the research revealed that the quality of integrated thematic learning increased. The first cycle of meetings one aspect of RPP 81,25%, teacher aspects 75,00%, and students 75,00%, meeting 2 aspects of observation RPP 87,5%, teacher aspects 85,72%, and aspects of learners 85,72%. Cycle 2 observes RPP 93,75%, teacher aspects 92,86%, and learners aspects 92,86%. This proves that the PBL model can improve the learning process of student.